Using primary healthcare facilities and patients’ expectations about triage system: Patients’ perspective from multisite Jordanian hospitals - Mohammad Minwer Alnaeem (19143733) (2024)
Background Using primary healthcare facilities can decrease the tension and workload in emergency departments (EDs). This study aim to examine the patient’s use of primary healthcare facilities before EDs visits and their expectations about the triage. Methods A cross-sectional design was utilized in at various EDs in different hospitals. A convenience sample of 726 patients were enrolled and completed a self-administrated questionnaire. Results The mean age of the participants was 38.1 (SD = 12.9). Most participants (68.2 %) did not have primary care physicians and did not want to know how long other patients waited (61.4 %). There are significant relationships between participants’ desired to know how long other patients have been waiting and their age (X2 = 4.02, P < .05), education level (X2 = 13.5, P < .001), and current job (X2 = 9.90, p < .05). Also, periodic updates from EDs staff about the delays were significantly related to participants’ age (X2 = 3.29), current job (X2 = 28.4), marital status (X2 = 8.93), and residency place (X2 = 9.94). Conclusion Educating patients about the triage system and the importance of using primary healthcare facilities is recommended to reduce ED waiting times and overload. Other Information Published in: International Emergency Nursing License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ienj.2024.101476